Pengembangan Bahan Ajar Dengan Strategi React Pada Mata Kuliah Struktur Aljabar I Di FKIP UMSU - Ellis Mardiana Panggabean (EduTech: Jurnal Ilmu Pendidikan dan Ilmu Sosial, 2015)
In designing a lesson, a lecturer need to consider what material should be taught, and how is the appropriate method to teach, and how to make sure that all students will learn the subject. Struktur Aljabar I is one of mathematic pure proficiency material at Mathematic departement. the characteristic of Struktur Aljabar has tight and cronological axiomatic deductive structure, full of abstract concept in definition or theorem. Therefore, Struktur Ajabar is difficult to learn and difficult to taught. that is why learning material and teaching activity is needed tobe directed in order to help the student to understand the link between the concepts, managing their own self learning, cooperating, and critical thinking. The aim of this study is to develop learning material by using REACT strategy at Struktur Aljabar I subject. This developing and trial research consist of design, limited trial application, and data analysis. descriptive analysis was used, and this research development produced a protoype Struktur Aljabar I material REACT base. Keywords: development, learning material, REACT strategy, Struktur Aljabar I